Children of heaven (Miramax : Buena Vista Home Entertainment, 1998)
Zohre's shoes are gone; her older brother Ali lost them. They are poor, there are no shoes for Zohre until they come up with an idea: they will share one pair of shoes, Ali's. School awaits. Will the plan succeed?